Prevalence of neutralizing antibodies to common respiratory viruses in intravenous immunoglobulin and in healthy donors in southern China - Tian, Xingui; Jiang, Zaixue; Ma, Qiang; Liu, Qian; Lu, Xiaomei; Liu, Wenkuan; Liao, Xiaohong; Zhou, Rong; Su, Xiaobo; Luo, Qingming (Journal of Thoracic Disease, 2016)
Background: Acute respiratory infections (ARIs) are a leading cause of death among children under the age of 5. However, there are no effective drugs for most of these severe viral infections. Passive immunotherapy with convalescent plasma or hyperimmune intravenous immunoglobulin (H-IVIG) is a potential therapeutic option for serious viral infections. It is important to find a suitable source of convalescent plasma and of H-IVIG containing high titer neutralizing antibodies (NAbs). Methods: Sera from 96 healthy adult donors in southern China and commercially available IVIG were analyzed for the titers of NAb to several most common respiratory viruses including respiratory syncytial virus (RSV), seasonal influenza A (InfA), enterovirus 71 (EV71), coxsackievirus A16 (CA16), adenovirus type 3 (Ad3) and a recent epidemic adenovirus type 55 (Ad55) by microneutralization test. Results: A high proportion of samples from healthy adult donors were positive for NAbs (>16) to all the viruses except Ad55. A different proportion of these samples had high NAb titers (>512) for InfA (25%), Ad3 (17.71%), RSV (9.38%), EV71 (1.04%), CA16 (3.13%), and Ad55 (4.17%). Commercially available IVIG had high NAb titers to InfA and Ad3 (>1,000) and lower NAb titers to RSV [320], EV71 [160], and CA16 [160]. Strikingly, IVIG also had a high NAb titer to Ad55 (>1,000). Conclusions: Convalescent plasma could be screened from healthy blood volunteers to establish blood banks and to prepare specific H-IVIG for treating severe ARIs caused by common respiratory viruses.